UKI: universal Kinect‐type controller by ICE Lab. (17th January 2017) - Paliyawan, Pujana; Thawonmas, Ruck
Summary: Universal Kinect‐type‐controller by ICE Lab (UKI, pronounced as 'You‐key') was developed to allow users to control any existing application by using body motions as inputs. The middleware works by converting detected motions into keyboard and/or mouse‐click events and sending them to a target application. This paper presents the structure and design of core modules, along with examples from real cases to illustrate how the middleware can be configured to fit a variety of applications. We present our designs for interfaces that decode all configuration details into a human‐interpretable language, and these interfaces significantly promote user experience and eliminate the need for programming skill. The performance of the middleware is evaluated on fighting‐game motion data, and we make the data publicly available so that they can be used in other researches. UKI welcomes its use by everyone without any restrictions on use; for instance, it can be used to promote healthy life through a means of gaming and/or used to conduct serious research on motion systems. The middleware serves as a shortcut in the development of motion applications—coding of an application to detect motions can be replaced with simple clicks on UKI. Copyright © 2017 John Wiley & Sons, Ltd.